Manganese superoxide dismutase: a regulator of T cell activation-induced oxidative signaling and cell death - Kamiński, Marcin; Röth, Daniel; Sass, Sabine; Sauer, Sven (Biochimica et biophysica acta, 2012)
Mitochondrial reactive oxygen species (ROS) are indispensible for T cell activation-induced expression of interleukin 2 (IL-2) and CD95 ligand (CD95L, FasL/Apo-1L) genes, and in turn, for CD95L-mediated activation-induced cell death (AICD). Here, we show that manganese superoxide dismutase (MnSOD/SOD2), a major mitochondrial antioxidative enzyme, constitutes an important control switch in the process of activation-induced oxidative signal generation in T cells. Analysis of the kinetics of T cell receptor (TCR)-triggered ROS production revealed a temporal association between higher MnSOD abundance/activity and a shut-down phase of oxidative signal generation. Transient or inducible MnSOD overexpression abrogated T cell activation-triggered mitochondrial ROS production as well as NF-κB- and AP-1-mediated transcription. Consequently, lowered expression of IL-2 and CD95L genes resulted in decreased IL-2 secretion and CD95L-dependent AICD. Moreover, upregulation of the mitochondrial MnSOD level is dependent on oxidation-sensitive transcription and not on the increase of mitochondrial mass. Thus, MnSOD-mediated negative feedback regulation of activation-induced mitochondrial ROS generation exemplifies a process of retrograde mitochondria-to-nucleus communication. Our finding underlines the critical role for MnSOD and mitochondria in the regulation of human T cell activation.